Susceptibility of limestone petrographic features to salt weathering : a scanning electron microscopy study - Alves, C. A. Simões (2013)
Salt weathering is a major erosive process affecting porous materials in buildings. There have been attempts to relate erosive mass loss to physical characteristics of materials, but in the case of natural stone it is necessary to consider the effect of petrographic features that are a source of heterogeneity. In this paper, we use scanning electron microscopy before and after salt weathering tests in cubic specimens of three limestone types (two grainstones and a travertine) in an attempt to built conceptual models that relate petrographic features and salt weathering susceptibility (represented by mass loss). In the grainstones, the most relevant feature in controlling salt weathering processes is the interface between micrite aggregates and sparry cement that constitute weakness surfaces and barriers to fluid migration. Given the small size of the heterogeneities in relation to the test sample dimension and their spatial distribution, the macroscopic erosive patterns are globally homogeneously distributed, affecting edges and corners. In the travertine specimens, there are macroheterogeneities related to the presence of detritic-rich portions that cause heterogeneous erosive patterns in the specimens. Petrological modeling helps to understand results of salt weathering tests, supporting field studies for natural stone selection.